A two-stage spark gap for blumlein-driven transversely excited atmospheric nitrogen laser - Kau, W.F.; Tou, T.Y.; Siew, W.O.; Yap, S.S.; Yang, R.B.; Chin, Oi Hoong (IOP Publishing, 2004)
A two-stage spark gap is used to implement a two-stage Blumlein circuit for the efficient operation of a transversely excited atmospheric nitrogen laser. This enables a more compact circuit arrangement which employs an array of doorknob capacitors as the dummy capacitors instead of large parallel-plate capacitors but maintains a comparable laser output performance.